A study of surface crack behaviour using heat treatment on mild steel - Muhammad Asyraf, Abd Talib (2008)
In the real industry life, welding is widely used and commonly can be found in any type of industries and the most common welding process is Shield Metal Arc Welding (SMAW). SMAW is used in this study because of the application of this type of welding is widely used and the cost of this welding is cheap. Welding common defect is crack. In order to solve the problem about crack from growing, a study on prevention of the crack is done in this study respected to the heat treatment. Although most of the industries using quenching as the common heat treatment process, the heat treatment itself is still applicable in determining the crack growth. So, the purpose of this study is to search and learn the effectiveness of annealing followed by normalizing in reducing the crack and preventing the crack growth. All specimen is take into consideration as all the specimen have the same crack but different length. First step in the process is to weld the workpiece and then observation is done using microscope to search the crack and mark. Heat treatment is done after marking process and observation at the crack was done to collect the data. Polishing was done after welding and heat treatment to reveal the crack. There is no comparison between the types of heat treatment effectiveness. The percentage of crack that was reduced was 41.1% as average number. Then the data obtained will be analyzed and a study is commencing in heat treatment toward crack growth prevention. At last, the heat treatment can be proving as one of the process for preventing crack other than physical treatment.